2001
DOI: 10.1002/ijc.1540
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and dosimetry of177Lu-DOTA-Y3-octreotate in a rat model

Abstract: ; 92:628 -633). In the current study, the toxicity and dosimetry of 177 Lu-DOTA-Y3-TATE were determined in both normal and tumor-bearing rats. Doses of 177 Lu-DOTA-Y3-TATE ranging from 0 to 123 mCi/kg were administered to rats and complete blood counts (CBCs) and blood chemistries were analyzed out to 6 weeks. No overt signs of toxicity were observed with 177 Lu-DOTA-Y3-TATE (i.e., lethargy, weight loss, scruffy coat or diarrhea) at any of the dose levels. Blood chemistries and CBCs were normal except for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…32, 33 Lewis et al showed kidney absorbed dose (0.670 mGy/MBq) from 177 Lu-DOTA-octreotate dose not indicate any probability of finding radiation damage in the rats kidneys with an injected activity of 555 MBq, leading to a renal dose of 0.37 Gy. 34 Compared to those results, 90 Y-DOTA-c(RGDfK) has the lower kidney absorbed dosimetry (0.568 mGy/MBq). In our radionuclide therapy, a maximum administrated activity were 33.3 MBq (11.1 MBq 3 3), leading to a renal dose of 0.019 Gy.…”
Section: Discussionmentioning
confidence: 77%
“…32, 33 Lewis et al showed kidney absorbed dose (0.670 mGy/MBq) from 177 Lu-DOTA-octreotate dose not indicate any probability of finding radiation damage in the rats kidneys with an injected activity of 555 MBq, leading to a renal dose of 0.37 Gy. 34 Compared to those results, 90 Y-DOTA-c(RGDfK) has the lower kidney absorbed dosimetry (0.568 mGy/MBq). In our radionuclide therapy, a maximum administrated activity were 33.3 MBq (11.1 MBq 3 3), leading to a renal dose of 0.019 Gy.…”
Section: Discussionmentioning
confidence: 77%
“…The discrepancy between different animal models is important, if absorbed dose estimations for humans are derived from animal models. The distribution of a radiopharmaceutical varies not only from rodents to humans, but obviously also between rats and mice [10,39,40] which is obvious even in our previous study on rats [10]. In this study, we predict and compare the absorbed dose from 68 Ga-ECC and 67 Ga-ECC.…”
Section: Discussionmentioning
confidence: 87%
“…The somatostatin receptor -positive rat pancreatic tumor (CA20948) model used in this study is well characterized and has been used in numerous similar studies at different centers to evaluate a variety of radiolabeled somatostatin analogues (29 -31). The doses of 213 Bi-DOTATOC administered for tumor treatment, acute, and chronic toxicity studies were each divided into two injections, separated by a 1-hour interval, to avoid potential mass effects and in consideration of previously established biological half-lives of the octreotide-based somatostatin analogues (27,30). Tumor growth inhibition was observed in both smalland large-volume tumors following treatment with 12.…”
mentioning
confidence: 99%